Ethical Dilemmas in Online News Portals: A Study on Tamil Language News Online Sites in Sri Lanka - Raguram, S. (Sri Lanka Development Journalist Forum, 2019)
The way in distributing and updating, the information has been drastically changing in recent past through the emerging new media. The sender and the receiver experience the attitudinal transformation in information path. In the post war era in Sri Lanka, the dimensions of online journalism particularly the vernacular Tamil language news portals shifts the parameters to rapid, gossip, personalization, intruding in private life and non-accountability from the horizons of ethical deliberations. The study employed the content analysis and approached the trends appeared in news online sites via expected ethical guidelines for the press in Sri Lanka and identified the deviations and the problematic pattern of functions.
Keywords: Online News Portals; Ethics of Press; Post War Era